ACR1, a yeast ATF/CREB repressor. - Vincent, A C (1992)
Members of the mammalian ATF/CREB family of transcription factors, which are associated with regulation by cyclic AMP and viral oncogenes, bind common DNA sequences (consensus TGACGTCA) via a bZIP domain. In the yeast Saccharomyces cerevisiae, ATF/CREB-like sequences confer either repression or activation of transcription, depending on the promoter context. By isolating mutations that alleviate the repression mediated by ATF/CREB sites, we define a new yeast gene, ACR1, which encodes an ATF/CREB transcriptional repressor. ACR1 contains a bZIP domain that is necessary for homodimer formation and specific DNA binding to an ATF/CREB site. Within the bZIP domain, ACR1 most strongly resembles the mammalian cyclic AMP-responsive transcriptional regulators CREB and CREM; it is less similar to GCN4 and YAP1, two previously described yeast bZIP transcriptional activators that recognize the related AP-1 sequence (consensus TGACTCA). Interestingly, deletion of the ACR1 gene causes increased transcription through ATF/CREB sites that does not depend on GCN4 or YAP1. Moreover, extracts from acr1 deletion strains contain one or more ATF/CREB-like DNA-binding activities. These genetic and biochemical observations suggest that S. cerevisiae contains a family of ATF/CREB proteins that function as transcriptional repressors or activators.